A numerical study on the effects of charge air temperature on the combustion and emission characteristics of a marine generator engine - Chien, Pham Van; Nam, Ngo Duy (Journal of Transportation Science and Technology, 2022)
A numerical study was carried out to investigate the effectiveness of the charge air cooling method on the exhaust gas emission reduction when applied to a four-stroke marine generator diesel engine at full load. The AVL FIRE 2018a software was used to perform three-dimension (3D) simulations of the combustion process and emission formations inside the engine cylinder operating with various charge air temperatures (CATs). The simulation results were then verified by measured values obtained from experiments in the Green Ship Technology laboratory (GSTLab), Korea. The simulation results showed In-Cylinder peak pressure increase tendencies as the CAT decreased from 360 K to 320 K, leading to an increase in the brake mean effective pressure (BMEP) by 10.74%. At the same time, the In-Cylinder peak temperature was decreased, resulting in a reduction in NO emission by 33.85%. Soot, CO, and CO2 emissions were also reduced by 63.92, 44.66, and 3.22%, respectively. In addition, the CAT cooling method also reduced specific fuel oil consumption (SFOC) by 9.68% due to the increase in the indicated efficiency. This study would be a useful material for operating engines in cases of trying to reduce exhaust gas emissions from existing engines without any additional emission post-treatment device.
Keywords: Charge air cooling; combustion; emission; nitric oxide; CO; CO2; soot; CFD analysis